Evaluasi Kualitas Sistem Informasi Manajemen Arsip Dinamis (SIMARDI) dengan Menggunakan Model Technology Acceptance Model (TAM) di Dinas Pertanian dan Perkebunan Aceh - Rosda, Rosda; Alfina (Jurnal Ilmu Komputer dan Teknologi Informasi, 2025)
The "SIMARDI" archival application program is one of the archival applications that can be implemented across all units managing correspondence in both government and private institutions, including the Agricultural and Plantation Office of Aceh. With its systematic and applicative processing capabilities, this application can assist in comprehensive archival management, including the proper and swift classification, orderly file arrangement, rapid and accurate archive data retrieval, as well as guiding the process of archiving reduction across all Regional Work Units (SKPD) and Regional-Owned Enterprises (BUMD)/State-Owned Enterprises (BUMN) within their respective areas. The acceptance of archivists towards the SIMARDI application is measured using the TAM (Technology Acceptance Model) method. This study aims to evaluate the implementation of the SIMARDI application using the TAM method, to understand the archivists' perceptions and the factors influencing their use of the application. The research method employed is quantitative, utilizing a questionnaire as a tool to collect data from 30 SIMARDI application users. The research results indicate that the archivists' acceptance of the SIMARDI application positively influences the three TAM variables: perceived ease of use (74%), perceived usefulness (72.57%), and technology acceptance (73.80%). These findings suggest that the developers should focus on improving the perceived usefulness variable of the SIMARDI application, as its percentage value is lower compared to the other variables.